New variants of the bottleneck tower of Hanoi problems - Majumdar, Abdullah Al Kafi (Journal of Bangladesh Academy of Sciences, 2021)
This paper considers two variants of the bottleneck Tower of Hanoi problems with n (≥1) discs and the bottleneck size b (≥2), which allows violation of the “divine rule” (at most) once. Denoting by MB3(n, b) the minimum number of moves required to solve the new variant of the bottleneck Tower of Hanoi problem, an explicit form of MB3(n, b) is found. Also, MB4(n, b) denotes the minimum number of moves required to solve the new variant of the bottleneck Reve’s puzzle, a closed-form expression of MB4(n, b) is derived. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 197-200, 2020